Beyond contribution of ionic liquids in nanostructuring polyaniline morphology; its effect on the properties of the polymerization medium - Fatima Al-Zohbi; Fouad Ghamouss; Bruno Schmaltz; Mohamed Abarbri; Khalil Cherry; Mohamad fadel Tabcheh; François Tran-Van (Nano Materials Science)
In the present work, the focus has been shifted to the relationship between the PANI morphology and the physicochemical properties, controlled by the amount of added ionic liquids, of the polymerization medium instead of focusing on the structure of the ionic liquids as used to be in the litterature. For that reason, PANI has been synthesized in different weight ratio of [Pyrr][PTS]/water following the standard experimental process. The addition of [Pyrr][PTS] into the polymerization medium controls the morphology of PANI without affecting its structure. Moreover, [Pyrr][PTS] promotes a viscous reaction system without the need of an external source. The viscosity of the polymerization system restricts the diffusion of species that leads to the predominance of the homogeneous nucleation mode during the course of polymerization and, thus, nanostructuring of PANI morphology. As for the ionic conductivity, it reflects the mobility of the ions of the polymerization medium and, thus, the way of its interference with the formed PANI that affects the arrangement and the shape of formed PANI fibers. This relationship between PANI morphology and the physicochemical properties, adjusted by adding ionic liquids, of the polymerization medium is prelaminar and promising. The effect of the ionic liquids on the viscosity as well as on the mobility of the polymerization medium have to be taken into consideration to choose the ionic liquids, which lead to the PANI with desired morphology.